A simplified theoretical model for the evaluation of structural behaviour of masonry spandrels. (16th August 2011) - Calderoni, Bruno; Cordasco, Emilia A.; Lenza, Pietro; Pacella, Gaetana
In this paper, a simplified theoretical model (named 'the arched strut'), useful for the evaluation of the structural behaviour of masonry spandrels subjected to shear, is proposed. It has been defined on the basis of the results of both numerical and experimental analyses performed on reduced scale specimens. The numerical analysis has been carried out in order to obtain confirmation of the collapse mechanisms observed during the experiments and information which cannot be directly obtained from testing and is difficult to obtain theoretically too, such as the extension of the effective area at the edges of the panel and the value of the horizontal component of the force acting in the strut. By means of the proposed model, theoretical expressions corresponding to the different observed failure mechanisms (toe-crushing and tension cracking) have been formulated. Finally, both experimental and theoretical findings have been compared with the Italian code requirements.